2019
DOI: 10.1093/chemse/bjz042
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bitter Taste Receptors and Solitary Chemosensory Cell Markers in the Human Sinonasal Cavity

Abstract: Abstract Some bitter taste receptors (TAS2R gene products) are expressed in the human sinonasal cavity and may function to detect airborne irritants. The expression of all 25 human bitter taste receptors and their location within the upper airway is not yet clear. The aim of this study is to characterize the presence and distribution of TAS2R transcripts and solitary chemosensory cells (SCCs) in different locations of the human sinonasal cavity. Biopsies were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The nasal mucosa is densely innervated by adrenergic and cholinergic nerve fibres, and the epithelium is innervated by interdigitating sensory nerve endings, mostly nociceptors (receptors that respond to noxious stimuli) 65 . In addition, nasal chemosensory cells that express bitter taste receptors may reflect a specialized sensory nerve system that reacts to noxious stimuli and bacterial products 66 . Cholinergic and adrenergic nerve fibres are activated through central reflexes initiated at the nasal mucosa by sensory nerves, including nociceptor C fibres.…”
Section: Role Of Nasal Nervesmentioning
confidence: 99%
“…The nasal mucosa is densely innervated by adrenergic and cholinergic nerve fibres, and the epithelium is innervated by interdigitating sensory nerve endings, mostly nociceptors (receptors that respond to noxious stimuli) 65 . In addition, nasal chemosensory cells that express bitter taste receptors may reflect a specialized sensory nerve system that reacts to noxious stimuli and bacterial products 66 . Cholinergic and adrenergic nerve fibres are activated through central reflexes initiated at the nasal mucosa by sensory nerves, including nociceptor C fibres.…”
Section: Role Of Nasal Nervesmentioning
confidence: 99%
“…The analysis of human sinonasal single-cell RNA sequencing data revealed that tuft cell markers are expressed at higher levels in the sinus than in the nasal cavity in patients with CRS, implicating tuft cells in the pathogenesis of CRSwNP. 71 It was further illustrated that SCCs and brush cells proliferate on exposure to aeroallergens, including fungal extracts (Aspergillus fumigatus and Alternaria alternata) 36,39 and after H1N1 influenza virus infection. 72 Recently, a gustducin and DCAMKL1-positive cell population was noted to be increased in human polyp tissue compared with turbinate tissue.…”
Section: Tuft Cells Are Enriched In Human Nasal Polyp Tissuementioning
confidence: 99%
“…Solitary chemosensory cells (SCCs) are found in healthy sinus cavity and turbinate tissues of the human upper airway where they function as epithelial sentinels by detecting pathogenic metabolites and initiate protective immune defense (106). Increased number of SCCs was found in the sinonasal epithelia of chronic rhinosinusitis with nasal polyps patients (107).…”
Section: Neuroimmune and Epithelial Interaction In Armentioning
confidence: 99%